The Differential Impacts of Contingent Employment on Fertility: Evidence from Australia - Mark Wooden; Trong-Anh Trinh; Irma Mooi-Reci (Institute of Labor Economics (IZA), 2021)
Many studies have reported evidence of negative associations between fixed-term contract employment and fertility. With few exceptions, these studies assume that employment status is exogenous and thus results are likely biased. Furthermore, previous research has mostly not considered whether the effects of employment status on fertility might vary with other worker characteristics. We draw on 19 years of data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey to investigate the association between contingent forms of employment (including both fixed-term and casual employment) and first births, and how that association varies with selected worker characteristics. The issue of endogeneity is addressed through the use of instrumental variables estimation. Our main finding is that both fixed-term contracts and casual employment are associated with a significantly lower probability of first births among men. We also find that these negative fertility effects vary with workers' education, occupational status, country of origin, age, and relationship status. The results for women suggest fixed-term contracts are actually associated with more births. However, in this case one of the instruments fails to satisfy the exclusion restriction, suggesting endogeneity remains a concern when analyzing female fertility outcomes and hence this finding should be given little weight.
Keywords: J13; J41; 330; Australia; contingent employment; employment instability; fertility; HILDA Survey; instrumental variables